The Effect of the Charge Transfer Transition of the Tetravalent Terbium on the Photostability of Oxide Thin‐Film Transistors. (7th July 2022) - Lan, Linfeng; Li, Xiao; Ding, Chunchun; Chen, Siting; Su, Huimin; Huang, Bo; Chen, Baozhong; Zhou, Hongkun; Peng, Junbiao
Abstract: The development of the next‐generation display technologies requires thin‐film transistors (TFTs) with high mobility and good negative‐bias‐illumination stress (NBIS) stability. Here, a tetravalent‐terbium‐doped indium oxide (Tb:In2 O3 ) semiconductor is reported, which can effectively improve the NBIS stability of the TFT while ensuring high mobility. The TFT with Tb:In2 O3 channel layer exhibited remarkable performance with a saturation mobility of 45.0 cm 2 V –1 s –1 (with average mobility of 38.6 cm 2 V –1 s –1 ), a turn‐on voltage ( V on ) of −1.1 V, and an on‐off current ratio of 10 8 . In addition, the Tb:In2 O3 TFT showed greatly improved NBIS stability with V on shift (Δ V on ) of −3.9 V (with average Δ V on of 4.0 V) under 3600 s stress with −20 V gate voltage and white light illumination (compared to Δ V on of −11.7 V for the pure In2 O3 TFT). Comprehensive studies reveal that the effective improvement of NBIS stability after Tb 4+ doping is mainly attributed to the wide‐band absorption of the incident blue light by the Tb4f 7 —O2p 6 to Tb4f 8 —O2p 5 charge transfer (CT) transition that has smaller overall lattice expansion/contraction and shorter relaxation time compared to VO ionization. Abstract : High‐mobility and high‐photostability thin‐film transistors based on a novel tetravalent‐terbium‐doped indium oxide (Tb:In2 O3 ) semiconductor are reported. The tetravalent terbium can effectively improve the stability under negative‐bias‐illumination stress (NBIS) due to the wide‐band absorption of the incident light by the 4f 7 to 4f 8 charge transfer transition.